1995
DOI: 10.1007/bf00034341
|View full text |Cite
|
Sign up to set email alerts
|

Tree species composition and rain forest-environment relationships in the middle Caquet� area, Colombia, NW Amazonia

Abstract: As part of an integrated forest vegetation and soil survey, tree species composition (DBH > 10 cm) was recorded in 95 plots of 0.1 ha, distributed over the principal physiographic units in the middle Caquet~i area, Colombian Amazonia. A total of 1077 tree species was found, classified into 271 genera and 60 families. Leguminosae and Sapotaceae show high familial importance values in all physiographic units. Lauraceae, Chrysobalanaceae, Moraceae, and Lecythidaceae are more important on well drained (flood plain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
126
7
10

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 56 publications
12
126
7
10
Order By: Relevance
“…Using pteridophytes and the family Melastomataceae, Tuomisto et al (2003a) demonstrated that environmental factors, especially soil type, were also important for species distribution and abundance patterns within terra firme forests in western Amazonia. Similar results were shown using the same taxa in a one-hectare plot in Ecuador (Poulsen et al, 2006), a 43-km long transect in northern Peru (Tuomisto et al, 2003b), palms in north-western Amazonia (Vormisto et al, 2004;Normand et al, 2006), species of trees with diameter ≥10 cm in specific areas in Colombia (Duivenvoorden, 1995), a network of 0.1 ha plots in south-western Amazonia (Phillips et al, 2003) and at a broader scale, using genera of trees from the whole of Amazonia (ter Steege et al, 2006).…”
Section: Is Regional-and Continental-scale Variation In Floristic Comsupporting
confidence: 63%
“…Using pteridophytes and the family Melastomataceae, Tuomisto et al (2003a) demonstrated that environmental factors, especially soil type, were also important for species distribution and abundance patterns within terra firme forests in western Amazonia. Similar results were shown using the same taxa in a one-hectare plot in Ecuador (Poulsen et al, 2006), a 43-km long transect in northern Peru (Tuomisto et al, 2003b), palms in north-western Amazonia (Vormisto et al, 2004;Normand et al, 2006), species of trees with diameter ≥10 cm in specific areas in Colombia (Duivenvoorden, 1995), a network of 0.1 ha plots in south-western Amazonia (Phillips et al, 2003) and at a broader scale, using genera of trees from the whole of Amazonia (ter Steege et al, 2006).…”
Section: Is Regional-and Continental-scale Variation In Floristic Comsupporting
confidence: 63%
“…1) are described and mapped in recent studies, carried out within the framework of the Tropenbos programme in Colombia Lips 1993, 1995;Duivenvoorden 1994Duivenvoorden , 1995Duivenvoorden , 1996Hoorn 1994;Van der Hammen et al 1992a,b). At Araracuara (Fig.…”
Section: Site Descriptionsmentioning
confidence: 99%
“…The surface of the leaves was measured using image-processing computer software (Adobe Photoshop). Methods of sampling and aria- a pH=7, NH4OAc method b Ca, Mg, K, Na, and P in HF/H2SO 4 extract after combustion 500 ~ C, N according to Kjehldahl method c I<DBH<10 cm, >2 m height at a DBH>10 cm lyses of mineralsoil, ectorganic horizons, forest composition, and forest structure are described in Duivenvoorden and Lips (1993, 1995) Lips and Duivenvoorden 1996and Duivenvoorden (1995, 1996.…”
Section: Site Descriptionsmentioning
confidence: 99%
“…The plateau and baixio sites in the present study are characterized by clayish and sandy soils, respectively, and baixio areas are seasonally inundated. Duivenvoorden (1996) reported that the canopy height was higher at well-drained sites than at poorly drained sites in an upper Amazonian region. Aiba and Kitayama (2002) suggested that the high allocation of biomass to height growth was related to productive …”
Section: Forest Structure and Biomassmentioning
confidence: 98%